Dementia with cardiac problems. (22nd July 2011) - Bute, Jennifer; Waller, Derek
Abstract : Jennifer Bute, a general practitioner, became aware of the first symptoms of dementia and cardiac problems around age 60. Since then, she has experienced episodic memory loss, loss of consciousness, and hallucinations